To Sir Phillip, with love - Quinn, Julia, 1970- (Quinn, Julia, 1970- Bridgerton series., 2021)
A widower and father Sir Phillip Crane proposes to his pen-pal, Eloise Bridgerton, believing her to be a homely spinster, so he is surprised to discover the beautiful, lively woman who appears on his doorstep.